Tanggung Jawab Orangtua Katolik dalam Pendidikan Iman Anak di Stasi Santo Yosef Kampung Baru - Rosalina Serly Irim (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2023)
This study aims to find out the forms of Catholic Parental Responsibility in Children's Faith Education, specifically in the field of koinonia, diakonia, and kerygma, which includes the forms of Catholic parental responsibility in children's faith education and the difficulties and challenges experienced by them. Catholic parents at St. Joseph Station Kampung Baru. This study uses a qualitative approach, observation, documentation and interviews from twelve informants are used to collect data. The results of this study indicate that responsibility is in various fields, such as koinonia which involves coaching in the form of gathering together in the family, giving advice on living in harmony, and teaching the values of mutual love; diakonia which includes coaching in terms of helping others, participating in church activities, and being involved in housework; as well as kerygma which prioritizes coaching such as reading and understanding the holy scriptures, giving reflections, and telling religious stories. However, several obstacles were also found, such as a lack of time between parents and children due to each other's busyness, challenges in managing time due to activities and work, and limited parental knowledge.